Renal dysfunction and 30-day mortality risk in patients with acute stroke - Busari, Abdulwasiu A; Amira, Christiana O; Bello, Babawale T; Okubadejo, Njideka U; Abdusalam, Ismail A; Ojini, Francis I (African Journal of Nephrology, 2019)
Background: Chronic kidney disease (CKD) and stroke constitute worldwide public health problems with rising incidence, prevalence and poor outcomes. While the link between renal dysfunction and myocardial infarction is well established, the link with stroke has been less well investigated. In this study, the prevalence and prognostic implication of renal dysfunction in patients admitted with acute stroke was assessed. Methods: This was a prospective observational study of 130 patients with first-ever stroke admitted within 7 days of stroke onset and followed up for 30 days. The study outcome measure was 30-day mortality. Stroke subtype was verified by a computerized tomography (CT) scan of the brain. Estimated glomerular filtration rate (eGFR) was calculated from serum creatinine using the 4-variable Modification of Diet in Renal Disease (MDRD) equation. Renal dysfunction was defined as eGFR < 60 mL/min/1.73 m2 and significant proteinuria was defined as urinary protein excretion ≥ 0.5 g in 24 hours. The Cox proportional hazards regression model was used to determine the relationship between GFR, proteinuria and 30-day mortality. Results: The majority of the patients studied (56%) were male and their mean age was 61.3 ± 13.9 years. Ischaemic stroke was the most common stroke subtype, accounting for 74% of all cases. Overall, 38% of patients had reduced eGFR < 60 mL/min/1.72 m2 while 35% had significant proteinuria. eGFR < 60 mL/min/1.73 m2 (hazard ratio, HR 3.59, 95% CI 1.03–13.26, p < 0.001) and proteinuria (HR 1.86, CI 1.00–8.14, p = 0.035) were independent predictors of mortality. Other independent predictors were age > 70 years, haemorrhagic stroke subtype, CNS score < 6.5 and random blood glucose > 7.8 mmol/L. Conclusions:Renal dysfunction is common among adult Nigerian patients with acute stroke. Both reduced eGFR and proteinuria were independent predictors of 30-day mortality in these patients.